Disruption of cellular immune response among male rotating night shift workers in Spain– The HORMONIT study - Harding, Barbara N.; Aguilar, Ruth; Espinosa, Ana; Castaño-Vinyals, Gemma; Papantoniou, Kyriaki; Navarrete, José Maria; Such Faro, Patricia; Torrejón, Antonio; Dobaño, Carlota; Moncunill, Gemma; Kogevinas, Manolis (Frontiers in Immunology, 2022)
Introduction Preliminary studies suggest that night shift work is associated with a desynchronization of rhythmic immune markers, possibly explaining the increased risk of infection, cardiometabolic disorders, and cancer in shift workers. Methods This study included 51 male rotating shift workers from a car industry in Barcelona, Spain, sampled twice toward the end of a 3-week night shift (22:00-06:00 h) and a 3-week day shift (06:00-14:00 h) rotation. We collected four blood samples per worker, at the start and end of each shift. We measured 27 cytokines, chemokines and growth factors in plasma samples by luminex using the Cytokine Human Magnetic 30-Plex Panel LHC6003M and applied linear mixed models to examine within-person associations between shift work and analytes’ concentrations, comparing samples taken at 06:00 h on a day and night shift. We also conducted a factor analysis using analyte concentrations from all 4 time points for each individual to identify common factors and determine if these factors were altered by shift work. Results We observed lower levels of 15 analytes in the night shift compared to the day shift including cytokines (pro-inflammatory TNF-α, IL-2R; anti-inflammatory IL1-RA; Th1 IL-2, Th2 IL-4 and Th17 Il-17), chemokines (IP-10, MIP-1α, MIP-1β, RANTES) and growth factors (EGF, G-CSF, HGF, VEGF, FGF). In a factor analysis, three factors were identified. The main factor (Factor 1), explaining 57% of the variance and including IL-1β, IL-12, IL-15, MIP-1α, MIP-1β, EGF and FGF; and another factor (Factor 3) explaining 10% of the variance and including the Th1 cytokine IL-12, were inversely associated with the night shift (coefficient: -0.17, 95%CI -0.32 to -0.01 and coefficient: -0.22, 95%CI -0.38, -0.06, for Factors 1 and 3, respectively). Our results indicate that night shift disrupts the levels of several immune markers, which could contribute to the increased risk of infections and cancer reported in night shift workers. Conclusion Night shift is associated with disruption of multiple immune response pathways.